Project Management and Problem Solving Methods in Management Consulting - Gábor, Richard (2011)
Conducting management consulting project for Transparency International Czech Republic, the leading non-profit non-governmental organization active in anti-corruption practices, by applying selected project management and problem solving methods, the objective of the thesis is to support the assumption that proper selection and application of suitable methods to problem identification, definition and decomposition enables to come up with the solution of the problem by analyzing it with no need for further solution development.